The synergistic effect of Thymus vulgaris essential oil and carvacrol with imipenem against carbapenem-resistant Acinetobacter baumannii: in vitro, molecular docking, and molecular dynamics studies - Jilani, Saoussen; Ferjeni, Mohamed; Al-Shammery, Kholoud; Rashid Mohammed AlTamimi, Haya; Besbes, Malek; Ahmed Lotfi, Salwa; Farouk, Amr; Ben Selma, Walid (Frontiers in Pharmacology, 2025)
BackgroundCarbapenem-resistant Acinetobacter baumannii (CRAB) is one of the most predominant causative agents of nosocomial infections, especially in the intensive care unit patients.ObjectiveThe current study investigates the antibacterial activities of Tunisian Thymus vulgaris essential oil (Thyme-EO) alone and in combination with imipenem against CRAB.MethodsThyme-EO antimicrobial activities were evaluated by disc diffusion and microdilution assays. Synergism between imipenem and Thyme-EO was determined by combined disc diffusion and checkerboard technique. The synergistic effect of the combined use of carvacrol and imipenem was evaluated by checkerboard assay. Interaction between the major compound identified by Gas Chromatography-Mass Spectrometry (GC/MS) of Thyme-EO and eight bacterial vital enzymes was analyzed by molecular docking and checked by molecular simulation for their stability.ResultsAccording to GC/MS analysis, carvacrol (78.83%) was the major component. The inhibition zones’ diameter by Thyme-EO varied from 18 to 36 mm. Importantly, the values of minimum inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) were of low level and ranged between 0.312 and 1.25 mg/mL. Interestingly, the MBC/MIC was equal to 1 for most tested bacterial strains, confirming a bactericidal effect of Thyme-EO. Combining imipenem and Thyme-EO diminished importantly the MIC of imipenem by 8- to 16-fold in the CRAB [fractional inhibitory concentration indexes (FICI) ˂ 0.5, synergy)]. Carvacrol showed antibacterial activities at low MIC levels of 64 and 128 μg/mL and advanced bactericidal effect justified by the MBC/MIC ratio, which was equal to 1 for most tested CRAB. Moreover, carvacrol interacts synergistically with imipenem against all bacterial isolates (FICI ˂ 0.5). The docking study demonstrated that carvacrol seemed to have high binding free energies (−8.1 kcal/mol) against D-alanine: D-alanine ligase (2ZDQ), which is implicated in the pathway of peptidoglycan’ biosynthesis. A 100-ns dynamic simulation investigation confirmed binding interactions and stability between carvacrol and the active residues of 2ZDQ.ConclusionThe current results demonstrated that carvacrol alone or combined with imipenem may constitute a promising opportunity as a novel strategy to treat infections caused by CRAB.